HUBUNGAN PENGETAHUAN TENTANG POLA HIDUP SEHAT (LIFESTYLE) DENGAN RISIKO SINDROM METABOLIK PADA LANSIA DI POSBINDU WILAYAH GEGERKALONG - Nida Nurhikmah; Hanifah Nurfikriyah; Rizka Ramadhani; Cyntia Navilandita; Putri Novitasari (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2026)
Healthy living is the aspiration of the elderly to maintain their ability to stay active in old age. This study aims to analyze the relationship between knowledge of a healthy lifestyle with metabolic syndrome risk in the elderly at Posbindu Gegerkalong. The research employed a quantitative descriptive method with a cross-sectional approach involving 20 elderly respondents selected with a purposive sampling method. The independent variables were knowledge of a healthy lifestyle, while the dependent variables included body mass index (BMI), blood pressure, and diabetes status. The results showed there is no significant relationship between knowledge level and BMI (P=0.55), blood pressure (P=0.11) and diabetes status (P=0.66). This result is in line with previous research by Wulandari and Santoso (2020), which states that the level of knowledge about healthy lifestyles does not always have a direct effect on a person's nutritional status. This can be caused by many external factors, such as eating habits, physical activity, and social environment.